Using Facebook™ to Recruit College-Age Men for a Human Papillomavirus Vaccine Trial. (March 2016) - Raviotta, Jonathan M.; Nowalk, Mary Patricia; Lin, Chyongchiou Jeng; Huang, Hsin-Hui; Zimmerman, Richard K.
College-age men were recruited using Facebook™ advertisements (ads), as well as traditional recruitment methods, for a randomized controlled trial to compare immunological responses to human papillomavirus vaccine administered in two dosing schedules. This study compares enrollees who were recruited through traditional recruitment methods versus social networking sites (SNSs), including Facebook. Potential participants were recruited using flyers posted on and off campus(es), and distributed at health fairs, classes, sporting, and other campus events; e-mails to students and student organizations; and print advertisements in student newspapers and on city buses. Facebook ads were displayed to users with specific age, geographic, and interest characteristics; ads were monitored daily to make adjustments to improve response. A total of 220 males, aged 18 to 25 years enrolled between October 2010 and May 2011. The majority of participants (51%) reported print advertisements as the method by which they first heard about the study, followed by personal contact (29%) and Facebook or other SNSs (20%). The likelihood of a SNS being the source by which the participant first heard about the study compared with traditional methods was increased if the participant reported (a) being homosexual or bisexual or (b) posting daily updates on SNSs. Facebook and other SNSs are a viable recruitment strategy for reaching potential clinical trial participants among groups who typically use social media to stay connected with their friends and hard-to-reach groups such as young men who self-identify as homosexual or bisexual.